UMP and Bosch Rexroth collaborate on automation engineering development - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 6 February 2023 - Universiti Malaysia Pahang (UMP) entered into a partnership with Bosch Rexroth Sdn. Bhd. (Bosch Rexroth) in curriculum development activities to strengthen university-industry collaboration.